2022
DOI: 10.26820/978-9942-602-31-2
|View full text |Cite
|
Sign up to set email alerts
|

Lectura y escritura académica y creativa: Instrumentos que aportan al desarrollo humano

Abstract: La lectura y la escritura son competencias que aportan de forma relevante al perfil de los profesionales del siglo xxi. Sin embargo, es necesario su estimulación y práctica para alcanzar los altos niveles requeridos por la academia. En tal sentido, la Red de Investigación Lectura y Escritura Académica LEA: “Cambiando vidas” y el Grupo de Investigación Innovaciones Pedagógicas para el Desarrollo Sostenible de la ULEAM acompañaron durante el periodo 2021 a estudiantes y profesorado de educación secundaria y univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The Ministry has acknowledged the crucial role of constant professional training of EFL teachers in the in-service (MinEduc, n.d.) sector to help teachers cope with the pedagogical and content challenges in implementing the curriculum in their classrooms. Several studies have revealed the lack of professional development programs for EFL in-service teachers in Ecuador (Burgin & Daniel, 2017;Villafuerte-Holguin & Macías-Mosquera, 2020); however, the few training programs implemented lack research to determine their effectiveness. According to Calle et al (2012Calle et al ( , 2015, it is necessary to expand research studies on the impact of professional development and teacher training while taking diverse educational contexts in Ecuadorian classrooms into account.…”
Section: Status Of Professional Development In Efl In Ecuadormentioning
confidence: 99%
“…The Ministry has acknowledged the crucial role of constant professional training of EFL teachers in the in-service (MinEduc, n.d.) sector to help teachers cope with the pedagogical and content challenges in implementing the curriculum in their classrooms. Several studies have revealed the lack of professional development programs for EFL in-service teachers in Ecuador (Burgin & Daniel, 2017;Villafuerte-Holguin & Macías-Mosquera, 2020); however, the few training programs implemented lack research to determine their effectiveness. According to Calle et al (2012Calle et al ( , 2015, it is necessary to expand research studies on the impact of professional development and teacher training while taking diverse educational contexts in Ecuadorian classrooms into account.…”
Section: Status Of Professional Development In Efl In Ecuadormentioning
confidence: 99%